Millimetre-wave magneto-optical determination of the anisotropic superconducting order parameter in the molecular superconductor (kappa)-(BEDT-TTF)(2)Cu(NCS)(2) - Schrama, J; Rzepniewski, E; Ardavan, A; Edwards, R; Singleton, J; Kurmoo, M; Day, P (1999)
We have used a novel millimetre-wave magneto-optical technique to study the angle-dependence of the high-frequency conductivity of the molecular superconductor kappa-(BEDT-TTF)(2)Cu(NCS)(2). The data, strongly suggest that the superconducting gap has nodes directed along the b and c directions of the crystal, in agreement with recent theoretical predictions. This supports the idea that the superconductivity in kappa-(BEDT-TTF)(2)Cu(NCS)(2) is d-wave in nature, and is mediated by spin fluctuations.